Metallic lithium composite material, and preparation method and application thereof
Patent Information
- Application Number
- CN202510439376.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2026-10-16
AI Technical Summary
该材料虽然设置了锂沉积诱导层,可诱导金属锂向内沉积,但最外层为金属材料,降低了复合材料的比容量
[0054](1)本申请提供的复合材料,所述金属锂复合材料包括含锂内核和双层茧体,内层茧体包括亲锂性三维石墨烯材料,外层茧体包括一维纳米碳材料,该结构设计使得双层茧体具有较大的比表面积和孔隙率,在金属锂沉积/剥离过程中起到类似弹簧的作用,有效适应金属锂的体积变化;
Smart Images

Figure CN122930852A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of lithium battery technology, specifically to a metallic lithium composite material, its preparation method, and its application. Background Technology
[0002] In recent years, with the depletion of fossil fuels and the increasing severity of environmental pollution, the new energy industry has received attention from governments worldwide and has developed rapidly globally. Among these, lithium-ion batteries are widely used in portable devices and electric vehicles due to their advantages such as high energy density, long lifespan, and lack of memory effect. However, the energy density of lithium-ion batteries is limited, making it difficult to meet the demands of higher energy applications.
[0003] Lithium metal anodes possess a higher specific capacity (3860 mAh / g), making them one of the ideal anode materials for high-energy-density batteries. However, due to the low toughness and high activity of lithium metal, lithium dendrite formation and volume expansion during charge and discharge processes limit its applications. Improving the stability and electrochemical performance of lithium metal has become an urgent problem to be solved.
[0004] CN116504973A discloses a lithium-carbon material with a cocoon structure. The cocoon structure includes a cocoon formed of structural carbon material and one or more lithium metal particles contained within the cocoon. Each lithium metal particle consists of a lithium metal core and an organic conductive layer coating the core surface. While this lithium-carbon material can partially solve the problems of lithium dendrite formation and volume expansion, it lacks lithiophilic deposition sites, resulting in uneven lithium metal deposition and poor cycle performance.
[0005] CN117525309A discloses a core-shell structured lithium metal composite material. This composite material uses lithium metal particles as its core, with a lithium deposition-inducing layer containing a lithiophilic material as an intermediate layer and a lithiophore-resistant volume expansion reserve layer as the outermost layer. Although this material has a lithium deposition-inducing layer to induce lithium metal deposition inwards, the outermost layer is a metallic material, which reduces the specific capacity of the composite material.
[0006] Therefore, how to develop a structurally stable lithium metal composite material that can simultaneously regulate the uniform deposition of lithium metal, and possess high specific capacity, long cycle life, and high-rate discharge capability, is a key problem that urgently needs to be solved. Summary of the Invention
[0007] In view of the problems existing in the prior art, the present invention proposes a novel lithium metal composite material. Through a structural design with a double cocoon on the surface of the lithium core, the outer cocoon regulates the uniform distribution of lithium ions and electrons, while the inner cocoon regulates the uniform distribution of electrons and induces uniform deposition of lithium metal. At the same time, it has a large specific surface area and rich pore structure, which can accommodate lithium metal. The outer and inner cocoons work together to suppress the generation and growth of lithium dendrites and improve the cycle performance and rate performance of the lithium metal anode.
[0008] To achieve this objective, the following technical solution is adopted in this application:
[0009] In a first aspect, this application provides a lithium metal composite material, the lithium metal composite material comprising a lithium-containing core and a bilayer cocoon disposed on the surface of the lithium-containing core, the bilayer cocoon comprising an inner cocoon of a lithiophilic three-dimensional graphene material and an outer cocoon of a one-dimensional nanocarbon material, the lithiophilic three-dimensional graphene material having a hierarchical porous structure, the lithiophilic sites being located inside or on the surface of the hierarchical porous structure.
[0010] In this invention, the lithiophilic three-dimensional graphene material has a large specific surface area and a hierarchical porous structure (containing micropores, mesopores, and macropores), which can support and anchor numerous lithiophilic deposition sites located inside or on the surface of the hierarchical porous structure. These lithiophilic sites can undergo in-situ alloying with the lithium-containing core, connecting the inner cocoon and the lithium-containing core, and can also induce lithium metal deposition inward. Simultaneously, it enhances the mechanical strength of the bilayer cocoon, giving it a spring-like function that can adapt to the volume changes of lithium metal during charging and discharging. The bilayer cocoon has a large specific surface area, porosity, and abundant porous structure, providing multiple channels for lithium-ion transport, homogenizing current distribution, effectively suppressing the generation and growth of lithium dendrites, and improving cycle life. The lithium metal composite material exhibits excellent cycle performance and rate performance, superior to lithium metal composite materials composed of a single one-dimensional nano-carbon material cocoon. Both bilayer cocoons are made of carbon-based materials, which are lightweight, resulting in a high specific capacity for the composite material.
[0011] Optionally, the lithium-containing core comprises metallic lithium and / or a lithium alloy, wherein the alloying element in the lithium alloy comprises at least one of tin, gold, barium, bismuth, calcium, germanium, platinum, lead, antimony, silver, boron, carbon, magnesium, indium, gallium, aluminum, or zinc.
[0012] Optionally, the lithium alloy contains more than 50% metallic lithium, preferably 60-95%.
[0013] Optionally, the average particle size of the lithium-containing core is 1-100 μm, preferably 5-50 μm.
[0014] Optionally, the one-dimensional carbon nanomaterial includes at least one of carbon nanofibers, single-walled carbon nanotubes, or multi-walled carbon nanotubes.
[0015] Optionally, the outer diameter of the one-dimensional carbon nanomaterial is ≤300nm, preferably 1-20nm, and more preferably 1-10nm.
[0016] Optionally, the length of the one-dimensional carbon nanomaterial is 1 μm to 500 μm, preferably 5-100 μm, and more preferably 10-50 μm.
[0017] Optionally, the BET specific surface area of the three-dimensional graphene is 1-1000 m² / g, preferably 5-500 m² / g.
[0018] Optionally, the size of the three-dimensional graphene material is smaller than the size of the lithium-containing core, preferably 1-20 micrometers, and more preferably 2-10 micrometers.
[0019] Optionally, the lithiophilic element in the lithiophilic three-dimensional graphene material includes at least one of tin, gold, barium, bismuth, calcium, germanium, platinum, lead, antimony, silver, boron, carbon, magnesium, indium, gallium, aluminum, or zinc.
[0020] Optionally, the mass ratio of the lithiophilic element to the three-dimensional graphene in the lithiophilic three-dimensional graphene material is 1:(1-50), preferably 1:(5-20).
[0021] Optionally, in the lithiophilic three-dimensional graphene material, the lithiophilicity of the lithiophilic element is weaker than that of the lithium-containing core.
[0022] As a preferred embodiment of the present invention, the mass ratio of the one-dimensional carbon nanomaterial to the lithiophilic three-dimensional graphene material is 1:(0.5-50), preferably 1:(1-20).
[0023] Optionally, the mass ratio of the double-layered cocoon to the lithium-containing core is 1:(0.1-300), preferably 1:(0.5-150), and more preferably 1:(2-100).
[0024] As a further preferred technical solution of the present invention, the thickness of the double-layered cocoon is 0.5-10μm, preferably 1-5μm;
[0025] Optionally, the ratio between the average particle size of the lithium-containing core and the thickness of the double cocoon is (1-20):1, preferably (5-10):1.
[0026] In a second aspect, the present invention provides a method for preparing the composite material described in the first aspect, the method comprising the following steps:
[0027] (1) A three-dimensional graphene material with a multi-level pore structure and a lithiophilic material are treated by at least one of the following methods: hydrothermal method, solvothermal method, vapor deposition method, atomic layer deposition method or vacuum evaporation method to obtain a lithiophilic three-dimensional graphene material.
[0028] (2) A lithium-loving three-dimensional graphene material, a lithium-containing core and a first organic solvent are mixed and then the inner cocoon is set on the surface of the lithium-containing core by high-speed winding or spray drying to obtain a lithium-loving composite material.
[0029] (3) Mix one-dimensional nano-carbon material, second organic solvent and lithium-loving composite material in step (1), and freeze-dry or spray-dry to set an outer cocoon on the surface of lithium-loving composite material to obtain the lithium metal composite material.
[0030] In step (1), the size of the three-dimensional graphene material is less than the size of the lithium core, and the organic solvents in steps (2) and (3) are inert to the lithium core (or do not undergo violent chemical reactions).
[0031] For example, the conditions for preparing lithiophilic three-dimensional graphene materials using the solvothermal method are as follows: Three-dimensional graphene and lithiophilic materials (such as silver nitrate, silver acetate, silver oxalate, etc.) are dispersed in an organic solvent such as ethanol, transferred to a stainless steel reactor, and reacted at 200-230℃ for 12-24 hours to obtain lithiophilic three-dimensional graphene materials. The hydrothermal method operates similarly to the solvothermal method, the difference being that the solvent contains water.
[0032] Conditions for preparing lithiophilic three-dimensional graphene materials by vacuum evaporation: using elemental lithiophilic material as the evaporation source and three-dimensional graphene material as the substrate, the content (mass percentage) of elemental lithiophilic material in three-dimensional graphene is controlled under vacuum by controlling the heating temperature, deposition rate and time.
[0033] Optionally, the size of the three-dimensional graphene material in step (1) is less than the size of the lithium-containing core, preferably 0.5-20 micrometers, and more preferably 1-10 micrometers.
[0034] In this invention, the size of the three-dimensional graphene material is controlled to be smaller than that of the lithium core, and the double-layer cocoon is set up by using different solvents in steps (2) and (3).
[0035] Optionally, the first organic solvent in step (2) includes at least one of the following: liquid alkane with 5-20 carbon atoms, liquid cycloalkanes with 5-20 carbon atoms, benzene, toluene, xylene, solvent oil D20, solvent oil D40, solvent oil D60, solvent oil D80, silicone oil, or light paraffin.
[0036] Optionally, the high-speed winding speed in step (2) is above 3000 rpm, preferably 5000-15000 rpm.
[0037] Optionally, the high-speed winding time is 5-90 minutes, preferably 10-60 minutes.
[0038] Optionally, the inlet air temperature for spray drying is 180~240℃, for example, it can be 180℃, 185℃, 190℃, 200℃, 210℃, 220℃, 230℃ or 240℃, etc., including but not limited to the values listed above, preferably 200~220℃.
[0039] Optionally, the outlet air temperature of the spray dryer is 80~120℃, for example, it can be 80℃, 85℃, 90℃, 100℃, 110℃ or 120℃, etc., including but not limited to the values listed above, preferably 100~110℃.
[0040] Optionally, the atomization pressure of the spray drying is 0.1~0.5 MPa, for example, it can be 0.1 MPa, 0.15 MPa, 0.2 MPa, 0.25 MPa, 0.3 MPa, 0.35 MPa, 0.4 MPa, 0.45 MPa or 0.5 MPa, etc., including but not limited to the values listed above, and preferably 0.2~0.4 MPa.
[0041] Optionally, the second organic solvent in step (3) includes at least one of dimethyl ether, dimethyl carbonate, fluoroethylene carbonate, 1,3-dioxolane, diethylene glycol dibutyl ether, 3-methoxypropionitrile, N-methylpyrrolidone, or N,N-dimethylformamide.
[0042] Optionally, the mixing in step (3) includes the following operations: mixing the one-dimensional carbon nanomaterial and the organic solvent once, and then adding the lithiophilic composite material for a second mixing.
[0043] Optionally, the mixing in step (3) may employ at least one of high-speed dispersion, high-pressure homogenization, or high-pressure turbulence.
[0044] Optionally, the pressure of the high-pressure homogenization and high-pressure turbulence is independently 500-2000 bar, preferably 600-1500 bar.
[0045] Optionally, the lithiophilic composite material is heat-treated prior to step (3).
[0046] Optionally, the heat treatment temperature is less than or equal to the melting point of the lithium-containing core.
[0047] Optionally, the heat treatment time is 0.5-5 hours, preferably 1-3 hours.
[0048] Optionally, the mass ratio of the one-dimensional carbon nanomaterial to the lithiophilic three-dimensional graphene material is 1:(0.5-50), preferably 1:(1-20).
[0049] Optionally, the mass ratio of the double-layered cocoon to the lithium-containing core is 1:(0.1-300), preferably 1:(0.5-150), and more preferably 1:(2-100).
[0050] Optionally, the thickness of the double-layered cocoon is 0.5-10 μm, preferably 1-5 μm;
[0051] Optionally, the ratio between the average particle size of the lithium-containing core and the thickness of the double cocoon is (1-20):1, preferably (5-10):1.
[0052] Thirdly, the present invention provides the application of the composite material as described in the first aspect above as the negative electrode active material of a lithium metal battery.
[0053] Compared with the prior art, this application has at least one of the following beneficial effects:
[0054] (1) The composite material provided in this application, wherein the lithium metal composite material includes a lithium core and a double cocoon, the inner cocoon includes a lithium-loving three-dimensional graphene material and the outer cocoon includes a one-dimensional nano carbon material. This structural design makes the double cocoon have a large specific surface area and porosity, which plays a similar role to a spring during the deposition / stripping of lithium metal, effectively adapting to the volume change of lithium metal.
[0055] (2) The lithium metal composite material provided by the present invention has a double cocoon structure design that can regulate the uniform distribution of lithium ions and electrons, which is conducive to the uniform and dense deposition of lithium metal inward, thereby inhibiting the generation and growth of lithium dendrites and improving the cycle performance and rate performance of lithium metal anode.
[0056] (3) Compared with the lithium metal composite materials in the prior art, the present invention uses one-dimensional nano carbon materials and lithium-loving three-dimensional graphene materials to construct a bilayer cocoon, which not only has good conductivity and wettability with lithium metal, but also has a low density, which is beneficial to improving the specific capacity of the electrode.
[0057] (4) By optimizing the structural design of the double-layer cocoon, such as the thickness of the cocoon and the ratio of one-dimensional nano-carbon materials and lithium-loving three-dimensional graphene materials, the present invention can further improve the energy density and cycle performance of the lithium metal anode.
[0058] (5) The preparation method provided in this application has a short process flow, high production efficiency, and is universally applicable. Attached Figure Description
[0059] Figure 1Here is a SEM image of the composite material in Example 2;
[0060] Figure 2 The cyclic test curves are for Examples 2, 4, and 8;
[0061] Figure 3 The cyclic test curves are for Examples 2, 9, and 11;
[0062] Figure 4 Cyclic test curves of Example 2, Comparative Example 4, and Comparative Example 5. Detailed Implementation
[0063] To facilitate understanding of this application, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of this application.
[0064] Example 1
[0065] This embodiment provides a lithium metal composite material, which includes lithium metal powder with a particle size of 50 μm and a double cocoon disposed on its surface. The inner cocoon includes a three-dimensional graphene material containing silver particles. The inner cocoon and the lithium-containing core are connected by an in-situ generated lithium-silver alloy. The outer cocoon is a double-walled carbon nanotube, which is connected to the inner cocoon by interweaving and entanglement.
[0066] The method for preparing the composite material includes the following steps:
[0067] (1) Dissolve 0.32g of silver nitrate in ethanol, and add 10g of three-dimensional graphene (purchased from Chihe New Materials Technology Nanjing Co., Ltd., with a specific surface area of 400-800m²). 2 / g, with 3-7 layers, pore size distribution of 30-80 nanometers, and average particle size of 5 micrometers) were ultrasonically treated and mixed evenly, and then transferred to a stainless steel reactor and reacted at 200℃ for 18 hours. The mass ratio of silver was 2%, and silver-containing three-dimensional graphene material was obtained.
[0068] (2) Mix 5g of silver-containing three-dimensional graphene material (10 micrometers, with a silver mass ratio of 2%), 0.51g of lithium metal powder and n-hexane, disperse at high speed at 8000rpm for 60min, set the silver-containing three-dimensional graphene material on the surface of lithium metal powder, and vacuum dry at 90℃ to obtain a lithium-loving composite material.
[0069] (3) Mix 0.1g of double-walled carbon nanotubes (purchased from Beijing Deco Island Gold Technology Co., Ltd., with an outer diameter of 2-4nm and a length of 5-15μm), dimethyl ether and the lithium-loving composite material in step (1), keep at 12000rpm for 20min, set the outer cocoon formed by double-walled carbon nanotubes on the surface of the lithium-loving composite material, freeze-dry, and obtain the lithium metal composite material.
[0070] Example 2
[0071] This embodiment provides a lithium metal composite material, which includes lithium silver powder with a particle size of 50 μm and a double cocoon disposed on its surface. The inner cocoon includes a three-dimensional graphene material containing tin particles. The inner cocoon and the lithium-containing core are connected by an in-situ generated lithium-tin alloy. The outer cocoon is a single-walled carbon nanotube, which is connected to the inner cocoon by interweaving and entanglement.
[0072] The method for preparing the composite material includes the following steps:
[0073] (1) Using elemental tin as the evaporation source and 10g of three-dimensional graphene (purchased from Shanghai Hydrogen Field New Material Technology Co., Ltd., with a specific surface area of 500m2 / g, 2-4 layers, pore size distribution of 500-1000 nanometers, and average particle size of 1 micrometer) as the substrate, tin was deposited onto the surface and interior of the multi-level pore structure in the three-dimensional graphene by vacuum evaporation, and the mass ratio of tin was controlled to be 50% to obtain tin-containing three-dimensional graphene material.
[0074] (2) Mix 0.5g of tin-containing three-dimensional graphene material (1 micrometer, tin mass percentage of 50%), 150g of lithium silver alloy powder (silver mass percentage of 5%) and solvent oil D40, disperse at high speed at 10000rpm for 45min, set tin-containing three-dimensional graphene material on the surface of lithium silver alloy powder, and vacuum dry at 120℃ to obtain lithium-loving composite material;
[0075] (3) 1g of single-walled carbon nanotubes (purchased from Shandong Carbon Seeking New Materials Co., Ltd., radius 1.4±0.5nm, length>100μm), N-methylpyrrolidone and the lithium-loving composite material in step (1) were mixed at 1000 bar for 90 min at 6000 prm and then spray-dried to form an outer cocoon of double-walled carbon nanotubes on the surface of the lithium-loving composite material. The inlet air temperature was 220℃, the outlet air temperature was 90℃, and the atomization pressure was 0.5 MPa to obtain the lithium metal composite material.
[0076] The lithium metal composite material obtained in step (2) was characterized by SEM. The characterization results are as follows: Figure 1As shown in the figure, it can be clearly seen that the three-dimensional graphene material forms an inner cocoon, and the outer cocoon covers the surface of the inner cocoon, constructing a double-layer cocoon.
[0077] Example 3
[0078] Compared with Example 2, the only difference is that the mass percentage of tin in the tin-containing three-dimensional graphene material is replaced with 16.7%, at which point the mass ratio of tin to three-dimensional graphene is 1:5, and all other conditions remain unchanged.
[0079] Example 4
[0080] Compared with Example 2, the only difference is that the mass percentage of tin in the tin-containing three-dimensional graphene material is replaced with 47.6%, at which point the mass ratio of tin to three-dimensional graphene is 1:20, and the other conditions remain unchanged.
[0081] Example 5
[0082] Compared with Example 2, the only difference is that the mass of the tin-containing three-dimensional graphene material is replaced with 1g, while the other conditions remain unchanged.
[0083] Example 6
[0084] Compared with Example 2, the only difference is that the mass of the tin-containing three-dimensional graphene material is replaced with 20g, while the other conditions remain unchanged.
[0085] Example 7
[0086] Compared with Example 2, the only difference is that the mass of lithium silver powder is replaced with 0.75g, while the other conditions remain unchanged.
[0087] Example 8
[0088] Compared with Example 2, the only difference is that the mass of lithium silver powder is replaced with 75g, while the other conditions remain unchanged.
[0089] Example 9
[0090] Compared with Example 2, the only difference is that lithium silver powder is replaced with lithium magnesium silver powder, with magnesium accounting for 5% of the mass and silver accounting for 5% of the mass, while the other conditions remain unchanged.
[0091] Example 10
[0092] Compared with Example 2, the only difference is that lithium silver powder is replaced with lithium boron indium powder, with boron accounting for 1% by mass and indium accounting for 4% by mass, while the other conditions remain unchanged.
[0093] Example 11
[0094] Compared with Example 2, the only difference is that the mass of the single-walled carbon nanotubes is replaced with 0.5g, while all other conditions remain the same.
[0095] Example 12
[0096] Compared with Example 2, the only difference is that the mass of the single-walled carbon nanotubes is replaced with 0.025g, while all other conditions remain unchanged.
[0097] Comparative Example 1
[0098] Compared with Example 2, the only difference is that the composite material includes cocoons formed by lithium silver particles and single-walled carbon nanotubes, but does not include cocoons formed by tin-containing three-dimensional graphene materials.
[0099] Comparative Example 2
[0100] Compared with Example 2, the only difference is that the composite material includes cocoons formed by lithium silver particles and tin-containing three-dimensional graphene materials, but does not include cocoons formed by single-walled carbon nanotubes.
[0101] Comparative Example 3
[0102] Compared to Example 2, the only difference is that the material includes lithium silver particles, but does not include the bilayer cocoon of single-walled carbon nanotubes and tin-containing three-dimensional graphene material.
[0103] Comparative Example 4
[0104] Compared with Example 2, the only difference is that the composite material includes lithium silver particles with a single-layer cocoon on the surface of the lithium silver particles. The single-layer cocoon is composed of single-walled carbon nanotubes and tin-containing three-dimensional graphene material, and does not form the double-layer cocoon as in this invention.
[0105] The preparation method includes the following steps: (1) 1g of single-walled carbon nanotubes, 0.5g of tin-containing three-dimensional graphene material (tin mass ratio is 50%), 150g of lithium silver alloy powder (silver mass ratio is 5%) and solvent oil D40 are mixed at 1000 bar and 6000 prm for 90 min. After spray drying, the inlet air temperature is 220℃, the outlet air temperature is 90℃, and the atomization pressure is 0.5 MPa to obtain the composite material.
[0106] Comparative Example 5
[0107] Compared with Example 2, the only difference is that the tin-containing three-dimensional graphene material is replaced with a tin-containing two-dimensional graphene material (the three-dimensional graphene material is replaced with a two-dimensional graphene material (purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd., XF021 7440-44-0)), and all other conditions remain the same.
[0108] Performance testing:
[0109] The materials from Examples 1-12 and Comparative Examples 1-5 were pressed onto copper foam to prepare electrodes. These electrodes were then assembled into symmetrical cells. The electrolyte was an ether-based solution purchased from Shenzhen Kejing Materials Technology Co., Ltd. The symmetrical cells were tested for cycle performance at 2 mA and 1 mAh, with the cutoff condition being the occurrence of a short circuit or an overpotential reaching 1 V.
[0110] Table 1
[0111]
[0112] As can be seen from Table 1:
[0113] (1) Comparing Examples 2 and 3-4, it can be seen that the number of cycles in Examples 3-4 is more than that in Example 2. This is because the mass ratio of tin to three-dimensional graphene in Examples 3-4 is more suitable, and the inner cocoon constructed by the tin-containing three-dimensional graphene material is more stable, which significantly improves the cycle performance; combined with Figure 2 It can be seen that the cycle time of Example 4 is longer than that of Example 2. In particular, under the conditions of 2mA and 1mAh, the relationship between the number of cycles and time is that one cycle can be performed in 1 hour.
[0114] (2) Comparing Example 2 and Example 5-6, it can be seen that the number of cycles in Example 5-6 is more than that in Example 2. This is because the mass of the tin-containing three-dimensional graphene material and the single-walled carbon nanotube in Example 5-6 is more suitable. The two work together to make the double-layer cocoon structure stable and can effectively adapt to the volume change of lithium metal during charging and discharging.
[0115] (3) Comparing Examples 2 and 7-8, it can be seen that the number of cycles in Examples 7-8 is greater than that in Example 2. This is because the mass ratio of lithium silver powder to the double-layer cocoon is more suitable in Examples 7 and 8, resulting in a longer cycle life of the composite material; combined with Figure 2 It can be seen that the cycle time of Example 8 is longer than that of Example 2, and the overpotential is smaller than that of Example 2, showing good cycle stability;
[0116] (4) Comparing Examples 2 and 9-10, it can be seen that the number of cycles in Examples 9-10 is more than that in Example 2. This is because the lithium core in Examples 9 and 10 is a ternary alloy, and the alloying elements have a better deposition effect on metallic lithium than binary alloys; combined with Figure 3 It can be seen that the cycle time of Example 9 is longer than that of Example 2, and it exhibits good cycle stability;
[0117] (5) Comparing Example 2 and Examples 11-12, it can be seen that the number of cycles in Example 2 is more than that in Examples 11-12. This is because the mass of single-walled carbon nanotubes in Examples 11-12 is less, resulting in a thinner outer cocoon and poorer adaptability to changes in the volume of metallic lithium; combined with Figure 3It can be seen that the cycle time of Example 11 is shorter than that of Example 2, and the overpotential reaches 1V faster than that of Example 2. This is because the outer cocoon of Example 11 is thinner, and the structural stability of the material is poor during the cycle.
[0118] (6) Comparing Example 2 and Comparative Examples 1-5, it can be seen that the number of cycles in Example 2 is more than that in Comparative Examples 1-4. This is because the cocoon composition materials and structures of the materials in Comparative Examples 1-5 are different from those in Example 2, and the stability of the structure and its adaptability to changes in the volume of metallic lithium are poorer; combined with Figure 4 It can be seen that although the overpotential in Comparative Example 4 was very low, a short circuit occurred quickly. This is because although Comparative Example 4 used three-dimensional graphene material, it did not form the structure of the present invention. The overpotential of Comparative Example 5 reached 1V faster than that of Example 2. This is because of the essential difference between the two-dimensional graphene material in Comparative Example 5 and the three-dimensional graphene material in Example 2: Three-dimensional graphene is a new type of carbon nanomaterial composed of two-dimensional graphene on a macroscopic scale. It can overcome the π-π interaction force between graphene sheets while maintaining the excellent characteristics of graphene's ultra-large specific surface area and ultra-high conductivity, effectively blocking the self-disordered stacking of graphene sheets and thus achieving the stability of its macroscopic structure. At the same time, three-dimensional graphene material has a multi-level porous structure, which is more conducive to the transport of lithium ions and the regulation of current density. As an inner cocoon, three-dimensional graphene can connect with the outer cocoon better than two-dimensional graphene.
[0119] The applicant declares that this application illustrates its detailed structural features through the above embodiments, but this application is not limited to the above detailed structural features, that is, it does not mean that this application must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvements to this application, equivalent substitutions of the components selected in this application, additions of auxiliary components, and selection of specific methods, etc., all fall within the protection scope and disclosure scope of this application.
Claims
1. A lithium metal composite material, characterized in that, The lithium metal composite material includes a lithium-containing core and a bilayer cocoon disposed on the surface of the lithium-containing core. The bilayer cocoon includes an inner cocoon of lithium-loving three-dimensional graphene material and an outer cocoon of one-dimensional nano-carbon material. The lithium-loving three-dimensional graphene material has a multi-level porous structure, and the lithium-loving sites are located inside or on the surface of the multi-level porous structure.
2. The composite material according to claim 1, characterized in that, The lithium-containing core includes metallic lithium and / or lithium alloys, wherein the alloying element in the lithium alloy includes at least one of tin, gold, barium, bismuth, calcium, germanium, platinum, lead, antimony, silver, boron, carbon, magnesium, indium, gallium, aluminum, or zinc. Preferably, the lithium alloy contains more than 50% metallic lithium, and more preferably 60-95% metallic lithium. Preferably, the average particle size of the lithium-containing core is 1-100 μm, and more preferably 5-50 μm.
3. The composite material according to claim 1 or 2, characterized in that, The one-dimensional carbon nanomaterial includes at least one of carbon nanofibers, single-walled carbon nanotubes, or multi-walled carbon nanotubes. Preferably, the outer diameter of the one-dimensional carbon nanomaterial is ≤300nm, more preferably 1-20nm, and even more preferably 1-10nm; Preferably, the length of the one-dimensional carbon nanomaterial is 1 μm to 500 μm, more preferably 5-100 μm, and even more preferably 10-50 μm.
4. The composite material according to any one of claims 1-3, characterized in that, The BET specific surface area of the lithiophilic three-dimensional graphene material is 1-1000 m² / g, preferably 5-500 m² / g; Preferably, the size of the three-dimensional graphene material is smaller than the size of the lithium-containing core, preferably 0.5-20 micrometers, and more preferably 1-10 micrometers; Preferably, the lithiophilic three-dimensional graphene material comprises at least one lithiophilic element selected from tin, gold, barium, bismuth, calcium, germanium, platinum, lead, antimony, silver, boron, carbon, magnesium, indium, gallium, aluminum, and zinc; Preferably, the mass ratio of the lithiophilic element to the three-dimensional graphene in the lithiophilic three-dimensional graphene material is 1:(1-50), more preferably 1:(5-20). Preferably, in the lithiophilic three-dimensional graphene material, the lithiophilicity of the lithiophilic element is weaker than that of the lithium-containing core.
5. The composite material according to any one of claims 1-4, characterized in that, The mass ratio of the one-dimensional carbon nanomaterial to the lithiophilic three-dimensional graphene material is 1:(0.5-50), preferably 1:(1-20). Preferably, the mass ratio of the double-layered cocoon to the lithium-containing core is 1:(0.1-300), more preferably 1:(0.5-150), and even more preferably 1:(2-100).
6. The composite material according to any one of claims 1-5, characterized in that, The thickness of the double-layered cocoon is 0.5-10 μm, preferably 1-5 μm; Preferably, the ratio between the average particle size of the lithium-containing core and the thickness of the double-layered cocoon is (1-20):1, and more preferably (5-10):
1.
7. A method for preparing the composite material according to any one of claims 1-6, characterized in that, The method includes the following steps: (1) Three-dimensional graphene material with multi-level pore structure and lithiophilic material are treated by at least one of hydrothermal method, vacuum heating method, solvothermal method, vapor deposition method, atomic layer deposition method or vacuum evaporation method to obtain lithiophilic three-dimensional graphene material. (2) A lithium-loving three-dimensional graphene material, a lithium-containing core and a first organic solvent are mixed and the mixture is wound at high speed or spray dried to form an inner cocoon on the surface of the lithium-containing core to obtain a lithium-loving composite material. (3) Mix one-dimensional nano-carbon material, second organic solvent and lithium-loving composite material in step (2), and form an outer cocoon on the surface of lithium-loving composite material by freeze drying or spray drying to obtain the lithium metal composite material. In both steps (2) and (3), the first organic solvent and the second organic solvent are inert to the lithium-containing core.
8. The method according to claim 7, characterized in that, In step (2), the first organic solvent includes at least one of the following: liquid alkanes with 5-20 carbon atoms, liquid cycloalkanes with 5-20 carbon atoms, benzene, toluene, xylene, solvent oil D20, solvent oil D40, solvent oil D60, solvent oil D80, silicone oil, or light paraffin. Preferably, the mixing in step (2) employs at least one of high-speed dispersion, high-pressure homogenization, or high-pressure turbulence; Preferably, the pressure of the high-pressure homogenization and high-pressure turbulence is independently 500-2000 bar, and more preferably 600-1500 bar.
9. The method according to claim 7 or 8, characterized in that, The second organic solvent in step (3) includes at least one of dimethyl ether, dimethyl carbonate, fluoroethylene carbonate, 1,3-dioxolane, diethylene glycol dibutyl ether, 3-methoxypropionitrile, N-methylpyrrolidone or N,N-dimethylformamide. Preferably, the mixing in step (3) includes the following operations: mixing the one-dimensional carbon nanomaterial and the organic solvent once, and then adding the lithiophilic composite material for a second mixing; Preferably, the lithiophilic composite material is heat-treated before step (3); Preferably, the temperature of the heat treatment is less than or equal to the melting point of the lithium-containing core; Preferably, the heat treatment time is 0.5-5 hours, and more preferably 1-3 hours.
10. The application of the composite material as described in any one of claims 1-6 as the negative electrode active material in a lithium metal battery.
Citation Information
Patent Citations
Metal lithium composite material with core-shell structure as well as preparation method and application of metal lithium composite material
CN117525309A